The efficacy of participatory communication training in farming communities : the case of Valley FM in the Cape Winelands District Region - Kafaar, Al-Ameen (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.